The The Role of Green Finance in Supporting the Sustainable Energy Transition in Indonesia: A Case Study on the Renewable Energy Sector: Green Finance - Setiyo Purwanto; Nur Endah Retno Wuryandari (Journal of Innovative and Creativity, 2025)
Green finance has become a strategic instrument in supporting the sustainable energy transition in Indonesia, especially in the development of the renewable energy sector. This study aims to identify the contribution of green finance to the growth of the renewable energy sector as well as its impact on the financial performance of energy companies in Indonesia. Using a case study approach, this study analyzes the financial data of energy companies and the green finance policies implemented. The research method uses a case study approach with the analysis of energy company financial data and green finance policies implemented in Indonesia. The study population consisted of energy companies operating in the renewable energy sector, with samples taken based on the availability of financial data and involvement in green finance. The results show that green finance significantly encourages increased investment in renewable energy projects, which contributes to accelerating the achievement of the national net-zero emission target. In addition, green finance also has a positive impact on the financial performance of energy companies, reflected in the increase in asset value and sustainable profitability. Supportive funding policies, including fiscal incentives and regulations that facilitate access to green capital, are key factors in the successful implementation of green finance. This study emphasizes the importance of integrating green finance policies in national energy development strategies to ensure environmental sustainability while increasing the competitiveness of the energy industry. These findings provide practical implications for policymakers and industry players in designing effective funding mechanisms to support the clean energy transition in Indonesia. Green finance not only serves as a financing tool, but also as a driver of economic transformation towards low-carbon development and recommends strengthening regulatory frameworks and building institutional capacity to expand scale and effectiveness in the future.